Analisis Perawatan Fasilitas Kantor pada Instansi X - Sinta Nurcahyani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
. This research aims to determine the maintenance of office facilities at Institute X, which includes the maintenance process and scheduling of office facility maintenance. This research uses a qualitative method with a descriptive approach, namely by describing and analyzing the problems found. The subjects of this research are four employees of Institute X for Finance, General Affairs, and Logistics. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The results of this research show that Institute X has carried out routine maintenance of office facilities, such as air conditioners and official vehicles. However, not all office facilities receive attention in their maintenance. This can be seen from the lack of lighting in the guest waiting room, which makes the room look dark. Then, there is no storage space or warehouse, which causes unused office equipment to be placed in the multipurpose room, where this room is also used as a meeting room.